Single-session dialectical behavior therapy skills training versus relaxation training for non-treatment-engaged suicidal adults: a randomized controlled trial. Issue 1 (December 2016) - Ward-Ciesielski, Erin; Jones, Connor; Wielgus, Madeline; Wilks, Chelsey; Linehan, Marsha
Abstract Background Individuals who are not engaged in treatment are commonly overlooked in the design of intervention trials targeting suicidal populations as a result of recruitment methodology that requires individuals to be referred from their current provider. In fact, research suggests that the majority of individuals who die by suicide have not been in contact with mental health services in the year before their death. Methods/design A randomized controlled trial of two brief, one-session interventions for adults who are not engaged in mental health treatment. Inclusion criteria include 1) 18 years or older, 2) experiencing suicidal ideation in the past week, 3) have not received mental health treatment in the month prior to screening, 4) living within commuting distance to the research office, and 5) willing to consent to recording and assessment. Exclusion criteria are 1) non-English speaking and 2) significant cognitive impairment. Recruitment takes place in the community via flyers, radio, and online advertisements. Interested individuals are screened via telephone and those who are eligible attend a one-time in-person assessment and intervention appointment. During this appointment, they are randomized to a single-session intervention in which they are presented with either dialectical behavior therapy skills or supportive discussion and instruction in relaxation. Following the in-person appointment, participants complete three follow-up interviews via telephone at one-week, four-weeks, and twelve-weeks post-intervention. The primary outcomes are suicidal ideation, emotion dysregulation, and skills use. Secondary outcomes include depression, anxiety, self-efficacy, and treatment utilization. Exploratory outcomes are suicidal and intentionally self-injurious behaviors. Intent-to-treat analyses will be conducted on primary and secondary outcomes. Discussion Suicidal individuals who are not engaged in mental health treatment are an understudied and significantly at-risk group for death by suicide. A better understanding of this population, targeted efforts to recruit and engage these individuals, and developing effective interventions for this group are critical areas for investigation in the field that this trial seeks to address. Trial registration Clinicaltrials.gov identifier:NCT02236325 ; Date of registration: 05-Sept-2014